KAJIAN MODAL SOSIAL PEKERJA DI KEBUN SAWIT KELURAHAN TANI AMAN KECAMATAN LOA JANAN ILIR KOTA SAMARINDA - Neneng Anjarwati; Rossy Mirasari; Fathiah (JURNAL AGRIMENT, 2020)
This researchis motivated by the role of social capital in helping increase the productivity of famers and workers, but not many people admit that increasing human capital increases productivity. This study aims to identify the social capital of workers in oil palm plantions and determine the lovels of social capital of wrkers in oil plam plantions. The data colection techniquis used in this study were directly in the field to distribute questionnaires and interview workers in the oil palm plantions. Then analyzed using the validity of an instrument. The results of this study are that the level of social capital, namely (trust, network, social norms) owned by workers in te oil palm plantion in Tani Aman Village Loa Janan ilir District Samarinda City is very large. With An average number of trusts of 96. And the decond is networks with an average number of 91.9. and the last is social norms with a ean number of 90.2 with the category of class intervals 88.5-105.2 stongly agree